(untitled) (Journal of the College of Education for Women, 2019)
Were not experience Khalil Hawi capillary module as presented or routine in the formatof the implications , but was saturated transitions quality that targeted built by visionary andmechanisms expressive , Valgosaidp when the container is a clash between two worlds worldNahdi to promote world on the ashes , and often strained poet himself to achieve an approachbetween worlds , and in the midst of those caesarean section exhausted poet in touch his toolsand visions , and this is why the poetry Hawi toward westernization expressive as a result ofthe conflict concepts chronic , be sure to researcher not engaged in the overall qualitativechanges in the structure and content, but the goal Acetknah level that qualitativetransformation Visionary First , the nature of employment in the automated charging thattransformation and enlightenment